EFFECT OF CORM AND CORM PIECES ON REGENERATION AND MULTIPLICATION OF ENSET (ENSETE VENTRICOSUM (WELW.) CHEESMAN) - Ashango, Taye Buke (International Journal of Research -GRANTHAALAYAH, 2017)
A field study was conducted on ‘enset’ propagation at Humbo, Wolayta. The experiments of this study were executed with the objectives of determining size of whole corms and corm pieces for better sucker production. Five whole corm sizes (0.75, 3, 7, 11and15 kg), five bigger (0.8, 1.75, 2.3, 3.5 and 4.6) and three smaller (0.2, 0.3 and 0.4 kg) corm pieces, three corm piece positions (lower, middle and top) of horizontal cut. There were significant (p<0.01) differences among corms and corm pieces in the number of suckers. Whole corms with 7 kg gave the highest number of suckers; similarly, corm pieces with 3.5 kg. The mean number of suckers produced ranged from 9.5-28.4 for whole corms, 3.7-38.1 for corm piece. There was no positive and significant relationship between total number of suckers and growth. Many of the other growth parameters are associated with each other. The highest sucker number was recorded using corms of 7 kg corm and 3.5 kg corm pieces. Significant variations among corms and corm pieces in the number of suckers formed, with whole corms, corms with 7 and 3 kg weights scored the highest number of suckers. With corm pieces, those with 3.5, 4.6, and1.75 kg sizes scored the highest sucker numbers. Compared for whole corms, corm pieces gave the greatest overall number of suckers. The size of corms and corm pieces had a significant effect on leaf width and leaf length; and sucker height, pseudostem length leaf width, leaf length and leaf number respectively. The position of the corm from which pieces were taken affected their regeneration capacity. Corm pieces from the apical end of the corm were able to regenerate.